Використання предикторів запалення для попередження ускладнень у хворих на сечокам'яну хворобу - Коломоєць, Юлія Сергіївна; Коломоец, Ю. С.; Kolomoiets, Y. S. (Державна установа «Інститут урології Національної академії медичних наук України», 2021)
Дисертація присвячена актуальній проблемі урологічної науки й практики, а саме покращенню результатів ранньої діагностики гострих інфекційних ускладнень нирок при сечокам’яній хворобі з порушенням уродинаміки, розробленню алгоритму лікування цієї категорії хворих на основі вивчення показників предикторів раннього гострого запального пошкодження нирок. Для вирішення поставлених завдань було проаналізовано результати обстеження та лікування 142 пацієнтів за період з 2018 по 2019 рр. Дослідження виконано на клінічній базі кафедри урології Запорізького державного медичного університету. Усіх хворих обстежено відповідно до чинних протоколів надання медичної допомоги МОЗ України. За результатами проведеного дослідження доведено, що важливим тестом для виявлення ранніх ознак інфекційно-запального процесу у хворих з порушенням уродинаміки при СКХ у перші 12–24 години є ІФА цитокіну (IL-1β) та предикторів пошкодження нирок (β2-мікроглобуліну та NGAL) у сечі, що проявлялось зниженням частоти ускладнень перебігу запального процесу в нирках під час проведення оцінки ефективності консервативної терапії у хворих без попереднього тестування. Установлено, що комбіноване використання предикторів запалення та загальноклінічних досліджень значно покращує диференційну діагностику запальних та гнійно-септичних ускладнень і тим самим дозволяє значно знизити частоту розвитку незворотних процесів у нирках та покращити результати лікування. Исследование посвящено актуальной проблеме урологической науки и практики, а именно улучшению результатов ранней диагностики острых инфекционных осложнений почек при мочекаменной болезни с нарушением уродинамики, разработке алгоритма лечения этой категории больных на основе изучения показателей предикторов раннего острого воспалительного повреждения почек. Все пациенты и здоровые лица, вошедшие в исследование, были разделены на III клинические группы. Распределение 70 пациентов проводилось по результатам ИФА мочи. Для определения референтных значений обследовано 30 условно здоровых лиц. С целью определения течения пиелонефрита и отдалённых осложнений после проведённого консервативного лечения проведен ретроспективный анализ историй болезни 42 пациентов с диагнозом МКБ, без определения результатов предикторов повреждения почек. По результатам проведенного исследования доказано, что важным тестом для выявления ранних признаков инфекционно-воспалительного процесса у больных с нарушением уродинамики при МКБ в первые 12–24 часа является ИФА цитокина (IL- 1β) и предикторов повреждения почек (β2-микроглобулина и NGAL) в моче, что проявлялось снижением частоты осложнений течения воспалительного процесса в почках при проведении оценки эффективности консервативной терапии у больных без предварительного тестирования. Установлено, что комбинированное использование предикторов воспаления и общеклинических исследований значительно улучшает дифференциальную диагностику воспалительных и гнойно-септических осложнений и тем самым позволяет значительно снизить частоту развития необратимых процессов в почках и улучшить результаты лечения. The dissertation is devoted to the topical problem of clinical urology - improving the results of early diagnosis of acute infectious kidney diseases in urolithiasis with urodynamic disorders, developing an algorithm for treating this category of patients based on the predictors of early acute inflammatory kidney damage. To solve the tasks, the results of examination and treatment of 142 patients for the period from 2018 to 2019 were analyzed. All patients were hospitalized in the urology department of "Hospital of Emergency and Ambulance". All patients and healthy individuals included in the study were divided into III clinical groups: I - patients with urolithiasis who underwent ELISA (n = 70). The average age was 46.0 (32.0; 61.5). Further distribution of patients in this group was performed based on the results of ELISA and general laboratory studies with mandatory consideration of clinical and anamnestic data, namely: IA - patients in whom the predictors of inflammation were within normal limits or there was an increase in one of the three indicators of markers of early renal damage (conservative therapy with subsequent general clinical laboratory control), (n = 48). IB - patients with an increase in the level of two or more indicators of predictors of inflammation (prescribed emergency surgical treatment), (n = 22). II - comparison - retrospective analysis of case histories of conservative treatment without determining the level of predictors of inflammation (n = 42). The average age was 45.5 (33.0; 57.0). ІІІ - control - conditionally clinically healthy persons, (n = 30). The average age was 37.0 (28.0; 51.0). The main criteria for inclusion in the study were women and men diagnosed with urolithiasis aged 18-90 years with the presence of stones / stones in the ureter (different localization) and signed informed consent to participate in the study. According to the results of a comparative study it is proved that ELISA cytokine (IL-1β) as well as predictors of renal damage (β2-microglobulin and NGAL) in urine of patients with urolithiasis are important tests to detect earlier preclinical signs of infectious and inflammatory complications. In the comparative characterization, MCP-1 had a statistically significant difference only between groups IB and III (P1B-3≤ 0.01). In the comparative analysis of IA and IB groups, no statistically significant difference was obtained (P≥0.05). Therefore, this marker has no informational value in the study. It has been reliably proven that the concentration of β2-microglobulin, IL-1β and NGAL in the first 12-24 hours significantly increases during the infectious-inflammatory process. When conducting a comparative analysis of general blood analysis in all three groups together, a statistically significant difference was found in the analysis of leukocytes when comparing groups IB and III (P1B-3≤0.01). In the analysis of other indicators, such as rod and erythrocyte sedimentation rate, no significant differences were obtained (P> 0.05). When conducting a comparative analysis of creatinine in all groups, it was found that statistically IA and IB groups (P≤0.05) are significantly different as well as groups IB and III (P≤0.05). In the analysis of IA group, in 25 patients (52,1%) the markers of early kidney damage were within normal limits, indicating the absence of infectious and inflammatory complications. Elevated levels of one of the three markers of early renal damage were found in 23 patients (47,9%). An increase in creatinine levels and the presence of leukocytosis with a shift of the leukocyte formula to the left was not observed in this group of patients. When analyzing the group IB (n = 22), all patients showed an increase in two or more indicators of inflammatory predictors, which indicated the presence of a pronounced infectious - inflammatory process. Leukocytosis with a shift of the leukocyte formula to the left, during hospitalization, was detected in 19 patients (86,4%), an increase in creatinine was found in 11 patients (50,0%). In order to determine the course of pyelonephritis and long-term complications after conservative therapy, without determining the level of predictors, a retrospective analysis of 42 case histories was performed. According to the obtained data, in patients of IA and IB groups there was a stable positive dynamic in laboratory parameters on the 10th day of treatment and on the 30th day after the start of therapy. In group II, on the contrary, there was a pronounced negative dynamic in the treatment. When analyzing the frequency of the next complications in the first 10-14 days of treatment, it was determined that the frequency of their occurrence in group II is 5 times more often than in group IA. When analyzing the long-term results (after 1 month) of treatment - the frequency of complications in group II is 3 times more often than in group IA. It is substantiated that at hospitalization of the patient with disturbance of urodynamic and increased level of one of three markers of early kidney damage, complex conservative therapy with the strengthened diagnostic control within 5-7 days is recommended. At independent untreated concretion - performance of planned surgical intervention is recommended. At aggravation of obstructive symptoms - carrying out urgent surgical treatment. In other cases, with an increase in two or more predictors of inflammation in patients with urolithiasis, hospitalization, regardless of the level of indicators of general laboratory tests, which would indicate the presence or absence of infectious-inflammatory process and the development of renal failure, it is recommended to perform urgent surgical intervention aimed at drainage of the affected kidney and removal of the calculus with subsequent administration of antibacterial, anti-inflammatory and infusion therapy
Использование предикторов воспаления для предупреждения осложнений у больных мочекаменной болезнью
The use of predictors of inflammation to prevent complications in patients with urolithiasis
Keywords: сечокам’яна хвороба; інфекційно-запальні ускладнення; гостра ниркова недостатність; хронічна хвороба нирок; предиктори запалення; мочекаменная болезнь; инфекционно-воспалительные осложнения; острая почечная недостаточность; хроническая болезнь почек; предикторы воспаления; urolithiasis; infectious-inflammatory complications; acute renal failure; chronic kidney disease; predictors of inflammation